Indonesian diaspora identity construction in a Southern Mindanao border crossing. - Talampas, Rolando (Asian Studies, 2015)
The Sangir and Marore migrants, called thus following their origins in North Sulawesi island regencies, have constituted the Indonesian diasporic groups in present-day Davao del Sur, South Cotabato, and Sarangani provinces, among others. Living in fishing and farming enclaves for generations, they have sought to escape from their poverty-stricken, neglected, and volcanic homeland. This study seeks to understand their “new beginnings” as diasporas through a survey of the social discourses obtaining in their communities. Indistinguishable from native Mindanaoans in physical characteristics, they relive and celebrate their cultural practices of tamo, tulude, and jontra with Filipinos, intermarry, acquire facility in Philippine languages, and integrate socially with locals who reside in the underdeveloped regions even as Indonesian consular services rally them behind the Indonesian flag. Interviews with identified Indonesians and their close Filipino associates sought to establish how their identities are being negotiated in their localities as they are far removed from official, national, and central calls for citizenship and patriotism.